2004
DOI: 10.1093/ndt/gfh525
|View full text |Cite
|
Sign up to set email alerts
|

Acute glomerulonephritis occurring during immunoadsorption with staphylococcal protein A column (Prosorba(R))

Abstract: This case series highlights the risk of GN among patients undergoing SPA immunoadsorption. The development of GN is associated with the presence of leukocytoclastic vasculitis. Patients with RA seem to be at particular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, this kind of therapy is slowly being replaced by B‐cell depletion therapies. Notably, the mode of action of immonoadsorption therapy and rarely occurring adverse effects (vasculitis, glomerulonephritis) 5 have not yet been cleared from the pathological point of view. Initially, it was suggested that immunoglobulins from plasma adsorb on a column on which protein A had been immobilized, as protein A displays a strong affinity to immunoglobulins.…”
Section: Introductionmentioning
confidence: 99%
“…However, this kind of therapy is slowly being replaced by B‐cell depletion therapies. Notably, the mode of action of immonoadsorption therapy and rarely occurring adverse effects (vasculitis, glomerulonephritis) 5 have not yet been cleared from the pathological point of view. Initially, it was suggested that immunoglobulins from plasma adsorb on a column on which protein A had been immobilized, as protein A displays a strong affinity to immunoglobulins.…”
Section: Introductionmentioning
confidence: 99%